1999
DOI: 10.1152/jappl.1999.86.3.1032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body temperature on the development of fatigue during prolonged exercise in the heat

Abstract: Nielsen. Influence of body temperature on the development of fatigue during prolonged exercise in the heat. J. Appl. Physiol. 86(3): 1032-1039, 1999.-We investigated whether fatigue during prolonged exercise in uncompensable hot environments occurred at the same critical level of hyperthermia when the initial value and the rate of increase in body temperature are altered. To examine the effect of initial body temperature [esophageal temperature (T es ) ϭ 35.9 Ϯ 0.2, 37.4 Ϯ 0.1, or 38.2 Ϯ 0.1 (SE)°C induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

41
741
21
24

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 891 publications
(837 citation statements)
references
References 38 publications
41
741
21
24
Order By: Relevance
“…Significantly different from * control and † rest (P Ͻ 0.05). (24,46), and the associated systemic dopamine response could be affected by sensory feedback arising secondary to the increased body temperature. Thus dopamine in the sympathetic ganglia is secreted mainly from the sensory neurons (3).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly different from * control and † rest (P Ͻ 0.05). (24,46), and the associated systemic dopamine response could be affected by sensory feedback arising secondary to the increased body temperature. Thus dopamine in the sympathetic ganglia is secreted mainly from the sensory neurons (3).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to exercise in the heat is thought to be primarily limited by thermoregulatory and fluid balance factors (8), and it has further been suggested that the central nervous system (CNS) may become important in the development of fatigue when body temperature is significantly elevated (15). Previous work conducted by Gonzalez-Alonso et al (6) concluded that a high internal body temperature (Tcore) per se causes fatigue in trained subjects during prolonged exercise in uncompensable hot environments. Hyperthermia has been demonstrate to exert a profound effect on the CNS, with a reduction in maximal muscle activity (17), altered EEG brain activity (16) and increased perceived exertion (18) reported when body temperature is elevated.…”
Section: Introductionmentioning
confidence: 99%
“…passive hyperthermia; recruitment curve; transcranial magnetic stimulation HIGH INTERNAL TEMPERATURE, ranging from 38.6 to 40.3°C, is associated with voluntary exhaustion during aerobic exercise, despite variations in baseline core temperature, heat storage rates, and final skin temperature (4,10). Similarly, hyperthermia has been shown to produce motor fatigue, evidenced by decreased voluntary activation during sustained maximal voluntary contractions (MVC) (16,34).…”
mentioning
confidence: 99%